Advances in local and ablative treatment of oligometastasis in prostate cancer. Issue 4 (25th August 2014) - Yao, Henry HI; Hong, Matthew KH; Corcoran, Niall M; Siva, Shankar; Foroudi, Farshad
Abstract Oligometastasis is a state of limited metastatic disease that may be amenable to aggressive local therapy to achieve long‐term survival. This review aims to explore the role of ablative radiotherapy and surgical management of prostate cancer (CaP) patients with oligometastasis. We performed a systematic review of the literature from November 2003 to November 2013 in the PubMed and EMBASE databases using structured search terms. From our literature search, we identified 13 cases of oligometastatic CaP managed by surgery. The longest disease‐free survival documented was 12 years following pulmonary metastasectomy. We also found 12 studies using radiotherapy to treat oligometastatic CaP with median follow‐up ranging from 6 to 43 months. Local control rates and overall survival at 3 years range from 66 to 90% and from 54 to 92%, respectively. Most patients did not report any significant toxicity. The limited current literature suggests oligometastatic CaP may be amenable to more aggressive local ablative therapy to achieve prolonged local control and delay to androgen deprivation therapy (ADT). There is a larger body of evidence supporting the use of radiotherapy than surgery in this disease state. However, no direct comparison with ADT is available to suggest an improvement in overall survival. Further studies are required to determine the role of aggressive‐targeted local therapy in oligometastatic CaP.